Post-Transcriptional Control of the Interferon System - Khabar, Khalid S. A. (2007)
The interferon (IFN) system is a well-controlled network of signaling, transcriptional, and post-transcriptional processes that orchestrate host defense against microbes. The IFN response comprises a multi-array of IFN-stimulated gene products that mediate a variety of biological processes designed to control infection and regulate specific immune responses. In this review, we focus on post-transcriptional mechanisms of gene regulation that occur during the course of IFN induction and during the response of cells to IFN. Post-transcriptional mechanisms involve different levels of regulation such as mRNA stability, alternative splicing, and translation. Such controls offer a fine tuning mechanism for efficient and rapid response and as a negative feedback control in IFN biosynthesis and response.